Samiska Fornlämningar Då, Nu & Alltid : En kvalitativ-komparativ litteraturstudie om dagens samiska relation till fornlämningar i det samiska kulturlandskapet - Lange, Christian (Linnéuniversitetet, Institutionen för kulturvetenskaper (KV), 2020)
The work investigates the relationship the Swedish indigenous people, the Sámi people, have towards their cultural remains in the Sámi cultural landscape. It is investigated through a qualitative-comparative literature studie which is primarily conducted through an analysis of four websites; two Sámi controlled websites and two swedish county administration controlled websites. The relationship the Sámi people have towards their ancient cultural remains can be seen through studies of their relationship towards graves and old settlement remains, (swe:kåtatomter) which reflects a relationship that is contested by factors such as the threat of exploitation of the Sámi cultural landscape, and by the challenges that comes with repatriation cases. The work emanates from a postcolonial perspective which can be seen throughout the entire work and which is primarily based on reconciliation as a concept within postcolonial theory